Cerebral blood flow velocity and autoregulation in paediatric patients following a global hypoxic-ischaemic insult. (May 2018) - Lovett, Marlina E.; Maa, Tensing; Chung, Melissa G.; O'Brien, Nicole F.
Abstract: Aim: To describe the cerebral blood flow velocity pattern and investigate cerebral autoregulation using transcranial Doppler ultrasonography (TCD) following a global hypoxic-ischaemic (HI) event in children. Methods: This was a prospective, observational study in a quaternary-level paediatric intensive care unit. Intubated children, newborn to 17 years admitted to the PICU following HI injury (asphyxia, drowning, cardiac arrest) were eligible for inclusion. TCD was performed daily until post-injury day 8, discharge, or death, whichever occurred earliest. Results: Twenty-six patients were enrolled. Median age was 3 years (0.33, 11.75), initial pH 6.95, and initial lactate 5.4. Median post-resuscitation Glasgow Coma Score was 3T. Across the entire cohort, cerebral blood flow velocity (CBFV) was near normal on day 1. Flow velocity increased to a maximum median value of 1.4 standard deviations above normal on day 3 and slowly downtrended back to baseline by the end of the study period. Median Paediatric Extended Version of the Glasgow Outcome Score was 4 at three months. No patient in the favourable outcome group had extreme CBFV on day one, and only one patient in the favourable group had extreme CBFV on PID 2. In contrast, 38% of patients in the unfavourable group had extreme CBFV on PID 1 (p=.039 compared to frequency in favourable group), and 55% had extreme CBFV on PID 2 (p = .023 compared to frequency in favourable group). No patient had consistently intact cerebral autoregulation throughout the study period. Conclusions: Following a HI event, patients with favourable neurologic outcomes had flow velocity near normal whereas unfavourable outcomes had more extreme flow velocity. Intermittently intact cerebral autoregulation was more frequently seen in those with favourable neurologic outcomes though return to the autoregulatory baseline appears delayed.